A general energy formula - Hare, Kathryn E.; Mohanty, Parasar; Roginskaya, Maria (MATHEMATICA SCANDINAVICA, 2007)
An analogue of the formula relating the Riesz energy of a measure on the torus with a weighted $l^{2}$ norm of its Fourier transform is given for energies arising from more general kernels. This involves estimating the Fourier transform of the kernel. The formula is used to study certain measures of (classical) energy dimension zero.